2005
DOI: 10.1364/ao.44.005763
|View full text |Cite
|
Sign up to set email alerts
|

Full-field vibrometry with digital Fresnel holography

Abstract: A setup that permits full-field vibration amplitude and phase retrieval with digital Fresnel holography is presented. Full reconstruction of the vibration is achieved with a three-step stroboscopic holographic recording, and an extraction algorithm is proposed. The finite temporal width of the illuminating light is considered in an investigation of the distortion of the measured amplitude and phase. In particular, a theoretical analysis is proposed and compared with numerical simulations that show good agreeme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
38
0

Year Published

2010
2010
2016
2016

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 49 publications
(38 citation statements)
references
References 26 publications
0
38
0
Order By: Relevance
“…Its influence has been described in [44,61,62]. The combined effect of amplitude and cyclic ratio was especially thoroughly discussed in [44]. In the present paper, we consider an intermediate recording regime that has not been discussed in literature: the quasi-time-averaging regime, for which the cyclic ratio can be qualified as moderate.…”
Section: Introductionmentioning
confidence: 95%
See 3 more Smart Citations
“…Its influence has been described in [44,61,62]. The combined effect of amplitude and cyclic ratio was especially thoroughly discussed in [44]. In the present paper, we consider an intermediate recording regime that has not been discussed in literature: the quasi-time-averaging regime, for which the cyclic ratio can be qualified as moderate.…”
Section: Introductionmentioning
confidence: 95%
“…Its value is related to the possibility to reconstruct, without any error, the vibration from a synchronous hologram sequence. In 2005, Leval et al [44] demonstrated the possibility to reconstruct the sinusoidal mechanical vibration by recording a sequence including three digital holograms. To do so, the holograms must be synchronously phaseshifted with the vibration and the cyclic ratio must satisfy α < 1∕Δφ m .…”
Section: Regimes For the Holographic Recordingmentioning
confidence: 99%
See 2 more Smart Citations
“…The measurement principle leads to a 3-frame phase shifting algorithms, described in [9], which allows the determination of 3D amplitude and phase of the movement.…”
Section: Experimental Set-upmentioning
confidence: 99%